Pengaruh Komunitas Belajar dan Literasi Digital Guru Terhadap Implementasi Kurikulum Merdeka SMPN 1 Nanga Pinoh - Nurany, Uni; Sabirin, Febrianto; Koriaty, Sri (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2025)
Abstract: Education in the digital era requires teachers to adapt to technological developments and dynamic curriculum changes. One of the government’s innovations to improve the quality of education is the implementation of the Merdeka Curriculum, which emphasizes flexible and student-centered learning. This study aims to determine the influence of Learning Communities (Kombel) and the Development of Teachers’ Digital Literacy on the Implementation of the Merdeka Curriculum at SMP Negeri 1 Nanga Pinoh, both partially and simultaneously. This research employed a quantitative approach with an ex post facto design. The population consisted of all 52 teachers at SMP Negeri 1 Nanga Pinoh, who were also selected as the sample using a saturated sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through descriptive analysis, prerequisite tests, and multiple linear regression. The results show that the Learning Community has a positive and significant effect on the implementation of the Merdeka Curriculum, contributing 50.1%, while Teachers’ Digital Literacy also has a positive and significant effect, contributing 78.0%. Simultaneously, both variables influence the implementation of the Merdeka Curriculum by 79.7%. These findings indicate that the more actively teachers participate in learning communities and the higher their level of digital literacy, the more optimal the implementation of the Merdeka Curriculum in schools. Therefore, strengthening teacher learning communities and enhancing teachers’ digital competencies are essential to ensuring the successful implementation of this educational policy. Keywords: Learning Community, Teachers’ Digital Literacy, Merdeka Curriculum Implementation